2016
DOI: 10.3174/ajnr.a4712
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Permeability Surface-Area Product as a Measure of Blood-Brain Barrier Permeability in a Murine Model

Abstract: Background and Purpose Permeability surface area product has been suggested as a marker for BBB permeability with potential applications in clinical care and research. However, few studies have demonstrated its correlation with actual quantitative measurements of BBB permeability. Our aim was to demonstrate the correlation of quantitative permeability surface area product and BBB permeability in a murine model by histologic confirmation. Materials and Methods Coronal MRI was performed on mice treated with ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
7
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 34 publications
1
7
0
Order By: Relevance
“…Our findings were consistent across subjects, as evidenced by the individual-subject DCE curves supporting our data being robust using these methods. Furthermore, our data are also concordant with other previously published animal model data, 5 and DCE-MR imaging-based human studies demonstrating increased hippocampal BBB permeability, 6 providing additional support from the literature.…”
supporting
confidence: 92%
“…Our findings were consistent across subjects, as evidenced by the individual-subject DCE curves supporting our data being robust using these methods. Furthermore, our data are also concordant with other previously published animal model data, 5 and DCE-MR imaging-based human studies demonstrating increased hippocampal BBB permeability, 6 providing additional support from the literature.…”
supporting
confidence: 92%
“…A review of the literature revealed that increased BBBP in the hippocampus has been previously demonstrated with DCE-MR imaging in control subjects in a mouse model of BBB disruption, in which histologic assessment of BBB integrity served as the reference standard. 7 Because the hippocampal microvasculature is supplied from both the anterior and posterior circulation, 4 hypothetic explanations have related the increased susceptibility of the hippocampus to cerebrovascular autoregulatory dysfunction that has been similarly described in the sympathetic vascular innervation of the posterior circulation. 10 Most important, there is molecular evidence for elevated expression of biomarkers of BBB disruption in the hippocampus.…”
Section: Discussionmentioning
confidence: 99%
“…5 Additionally, animal studies have revealed increased protein expression of CD36, matrix metalloproteinase-13, and osteopontin correlated with increased hippocampal BBBP, 6 and dynamic contrast-enhanced (DCE)-MR imaging-derived baseline contrast enhancement curves were highest in the hippocampi in control subjects. 7 The purpose of our study was to evaluate region-specific BBBP metrics in healthy human subjects.…”
mentioning
confidence: 99%
“…Unlike blood vessels in other parts of the body, the permeability of central nervous system (CNS) vasculatures is also regulated by the specialized blood‐brain‐barrier. For CNS vessels, the permeability surface‐area product (PS) has been used as a marker for blood‐brain‐barrier permeability . We found that PS was highest in IgG‐treated group, indicting more plasma efflux from vessels, and dropped significantly in the DC101‐treated groups.…”
mentioning
confidence: 86%